2019
DOI: 10.1177/0739456x19883000
|View full text |Cite
|
Sign up to set email alerts
|

Why Does Planning Matter in Microclimate Management and Urban Heat Mitigation?

Abstract: In this paper, we examine two mixed-use redevelopment projects in the United States, including both regulatory and procedural contexts, to assess how decision-making processes affected microclimate outcomes. We investigate Belmar in Lakewood, CO and 29th Street Mall in Boulder, CO. Measurements and simulations of microclimate show that Belmar mitigates urban heat more effectively. Policies including building height, street patterns, and landscaping standards were key variables in this outcome. Through intervie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Other strategies "green" the urban environment, ranging from green roofs to expanding urban tree canopies (Berke and Stevens 2016;Burgess and Foster 2019;Mahlkow and Donner 2017;Stone et al 2019;Stone et al 2014). 3 Additional strategies range from enhancing building and transportation energy efficiency to designing urban forms that increase thermal comfort (Burgess and Foster 2019;Heris, Middel, and Muller 2020;Heris, Muller, and Wilson 2019;Stone et al 2019).…”
Section: Urban Heat Management and Heat Wave Response Planningmentioning
confidence: 99%
“…Other strategies "green" the urban environment, ranging from green roofs to expanding urban tree canopies (Berke and Stevens 2016;Burgess and Foster 2019;Mahlkow and Donner 2017;Stone et al 2019;Stone et al 2014). 3 Additional strategies range from enhancing building and transportation energy efficiency to designing urban forms that increase thermal comfort (Burgess and Foster 2019;Heris, Middel, and Muller 2020;Heris, Muller, and Wilson 2019;Stone et al 2019).…”
Section: Urban Heat Management and Heat Wave Response Planningmentioning
confidence: 99%
“…To overcome the limitations of Stone Jr. et al’s [ 13 ] scenario, Heris et al [ 164 ] suggested a framework wherein they approach microclimate management as development management. They found five main factors shaping the policy choices taken to mitigate urban heating: (1) urban vision, (2) land use and form controls, (3) design guidelines, (4) public financing, and (5) ownership/condemnation.…”
Section: Discussionmentioning
confidence: 99%